Cystic angiomatosis, a heterogeneous condition: Four new cases and a literature review. Issue 43 (October 2016) - Najm, Aurélie; Soltner-Neel, Elise; Le Goff, Benoît; Guillot, Pascale; Maugars, Yves; Berthelot, Jean-Marie
Abstract: Background: Cystic angiomatosis (CA) is a rare disorder causing bony cysts. It displays some similarity to Gorham–Stout disease (GSD), but has a much better local prognosis, despite the larger number of cysts. These 2 conditions also differ in terms of their location, visceral involvement, and response to treatment. Methods: We report 4 cases of CA, including 1 sclerosing form, which we compare with cases from a literature review performed with PRISMA methodology. Results: We reviewed 38 articles describing 44 other patients. Mean age at diagnosis for the 48 patients (our 4 patients + the 44 from the review) was 22.5 years, and 28 of the patients were men. The femur was involved in 81% (n = 39), the pelvis in 73% (n = 35), the humerus in 52% (n = 25), the skull in 48% (n = 23), and the vertebrae in 44% (n = 21). Visceral lymphangiomatosis (either clinical, or detected on autopsy) was also reported in 35% (n = 18) of the patients. The spleen was the most frequently involved organ (n = 12), followed by the lungs and pleura (n = 8). Liver cysts and/or chylothorax were rarely reported (5 cases), but were invariably fatal. Radiation therapy on bone or soft tissue masses was ineffective, as was interferon alpha, in the 2 patients in which this drug was tested. The efficacy of bisphosphonate was at best equivocal. Conclusion: The progression of CA is unpredictable and treatments effective against GSD, such as bisphosphonates and radiotherapy, have proved ineffective for this condition. New treatments are thus urgently required.